Examination of genotype × environment interactions by GGE biplot analysis in spring durum wheat - Kendal, Enver; Sener, Okan (The Indian Journal of Genetics and Plant Breeding, 2016)
A study was conducted to examine the effects of genotype × environment interaction (GEI) on grain yield, its components, and quality characteristics using genotype main effect (G) plus genotype × environment interaction (GE) (GGE) biplot analysis. Significant differences were observed among cultivars in grain yield, yield components, and quality traits and the relationship between yield components was used to identify three groups. Positive correlations were found between quality parameters and yield components, whereas correlations of quality parameters with yield and yield components were negative. The GGE biplot indicated that E6 (single irrigated location at Diyarbakir) was an ideal environment for all traits and E5 (rainfed locations at Diyarbakir) was a highly efficient model for quality parameters. The biplot analysis showed that Zenit was the best cultivar in terms of yield and quality and Zühre was efficient for quality parameters only and hence these two genotypes can be recommended to Southeastern Anatolia Region in Turkey.